Population dynamics and infectious diseases in Asia - Sleigh, Adrian; Leng, Chee Heng; Yeoh, Brenda SA; Hong, Phua Kai; Safman, Rachel (World Scientific Publishing Co.Pte Ltd., 2006)
Stimulated by a scholarly workshop convened in Singapore in late 2004, this volume considers the potentially lethal pattern of infectious disease emergence in Asia. It explores the causes and consequences of infectious agents in the region historically and examines such newly emergent natural biological threats as SARS and avian influenza